112 Parkinson's disease and sociodemographic factors: a review. Issue 9 (12th August 2022) - Wu, Kit; Vidot, Micha; Mitchell, James W; Nitkunan, Arani; Carr, Georgina
Abstract : Background: Unwarranted variation in treatment, care and support for people with Parkinson's Disease (PD) is well documented. To improve equity of service, in line with the NHS Long Term Plan, it is imperative that we understand how sociodemographic factors affect management and care of PD. Aim: To review published literature between sociodemographic factors and clinical factors, diagnosis, treatment and outcomes for people with PD. Method: We conducted a focused review of published literature between 2000-2021 to outline the evidence describing the relationship between the ten protected characteristics of the Equality Act 2010 and clinical factors, treatment and outcomes in PD. Other factors such as deprivation, settlement status, education and employment were also explored. Results: There is an abundance of published literature on age, disability, sex and gender over the twenty- year period. Studies on race and education and employment yielded mixed results. Evidence is lacking for gender reassignment, marriage and civil partnership, pregnancy and maternity, religion and belief, sexual orientation, deprivation, geographical variation (within UK), immigration and settlement. Discussion: PD impacts on many facets of life. This review has identified many gaps in knowledge of the effect of sociodemographic factors affecting PD. More research is needed to better provide a more equitable service to patients.